Représentations du système de justice criminelle : essai de typologie - Robert, Philippe; Faugeron, Claude (Acta Criminologica)

(untitled) (Les Presses de l'Université de Montréal, 1973)
AbstractIMAGE OF THE CRIMINAL JUSTICE SYSTEM TYPOLOGY STUDYThe present crisis in criminal justice — in France as in many other countries — shows two remarkable characteristics. On the one hand, the crisis is universal and is one that concerns the function assigned or credited to this system of criminal justice in society ; this places the system's image in some doubt in various sectors of society. On the other hand, this crisis defies all attempts at partial reform. Many schools of criminal policy have tried them in vain. Criminology has begun to rediscover that the science of crime and of the criminal — the progression from concept to commission of the act — also involves the reaction of society to the criminal phenomenon. But only too often, this progression is regarded as a poorly specified interaction, quite commonplace, or as a breakdown in simple technology. Only an integrated scientific approach — inclusive of the concept of the social image — can say something new and decisive in such a situation.This study belongs to one of the many research projects which the scientific programme of the S.E.P.C. is organizing, that devoted to the image of criminal justice in society.A questionnaire was distributed to a sample population in France, limited in size, but sufficient to validate the anticipated analysis (200). Each person was chosen according to several criteria (sex, age, socio-professional category, place of residence) in order to make sure of the presence of all the characteristics anticipated. The ecological variable was controlled by interviewing persons in four sectors of the 15th arrondissement of Paris (wealthy older district, middle class older district, renovated wealthy district, renovated middle class national housing), in the suburbs of Paris (Bobigny cottages and Bobigny national housing), at Epinal and in the region of Auch.The authors established a hypothesis according to which the organization of the dependent variable rests on a typology of conformism.The authors thought that the dimension of conformism was complex and tried to outline its components. According to their results, there is a resistance to change. It seems to be closely linked — even though in a wide variety of circumstances — with an optimism/pessimism dimension (where manicheism seems to be identified as one of the circumstances). To tell the truth, the authors do not know if resistance to change and optimism/pessimism are two autonomous, albeit connected dimensions, or two components of conformism. They will come back to this in future studies. They conclude by saying that conformism is clearly related to the image of criminal justice.